FITNESS TRAINING IN THE EDUCATION OF STUDENTS - Yakubjonov Ikrom Akramjonovich; Yakubjonova Feruzaxon Ismoilovna (International Journal of Innovations in Engineering Research and Technology, 2023)
The article discusses the features of conducting physical education classes with students of non-specialized universities. The characteristic of non-standard means and forms of their implementation is given. The authors present fitness tools used in working with students, contributing to improving the efficiency of the educational process.